(untitled) (Singapore, 1986)
A text containing a selection of review articles on the following topics: quantum control of molecular dynamics, modern perspective on coherent control, molecular engineering of push-pull choromophores, time-resolved pumped sum-frequency generation spectroscopy, and related topics.
Keywords: Multiphoton processes,Spectrum analysis,Laser spectroscopy,Molecular spectra